A blazar as the likely counterpart to 4FGL J0647.7−4418 instead of a gamma-ray binary. Issue 3 (11th January 2020) - Martí, Josep; Sánchez-Ayaso, Estrella; Luque-Escamilla, Pedro L; Paredes, Josep M; Bosch-Ramon, Valentí; Corbet, Robin H D
ABSTRACT: The persistent gamma-ray source 4FGL J0647.7−4418 is tentatively associated in the latest Fermi catalogue with the subdwarf O-type X-ray binary HD 49798. However, an active galactic nucleus (AGN) candidate is also mentioned as an alternative identification in updated versions of the catalogue accompanying paper. If the first association were correct, this would add HD 49798 to the handful of currently known gamma-ray binaries, and therefore represent a significant breakthrough not only because of a new member addition, but also because of the apparent white dwarf companion in this system. Despite these perspectives, here, we show that the stellar association is likely wrong and that the proposed AGN object, well inside the Fermi 95 per cent confidence ellipse, is a more conceivable counterpart candidate to the Fermi source due to its strong blazar similarities.